Caracterização espectral da água do reservatório de Itupararanga, SP, a partir de imagens hiperespectrais hyperion e análise derivativa - Ennes, Rejane [UNESP]; Galo, Maria de Lourdes Bueno Trindade [UNESP]; Tachibana, Vilma Mayumi [UNESP] (Universidade Federal do Paraná (UFPR), Centro Politecnico, 2010)
The current accessibility to hyperspectral images of Hyperion/EO1 orbital sensor has brought new perspectives for studies of aquatic environments for allowing the remote estimative of several optically active constituents (OACs) in water body. The changes in the composition and concentration of OACs cause different patterns of absorption and scattering of electromagnetic radiation, likely to be detected using hyperspectral data. Therefore, an investigation was conducted taking into account the spectral characterization of water of a reservoir intended for public supply (Itupararanga Reservoir), from Hyperion/EO1 images and derivative analysis technique applied to spectral curves generated. Simultaneously to the acquisition of a Hyperion/EO1 image, a field campaign was carried out to collect limnological data in situ in georeferenced points. After radiometric correction of the image, reflectance curves of pixels were extracted for each station and the curves obtained were subjected to the technique of derivative analysis, which revealed features of absorption and scattering mainly associated to the presence of algal pigments. The results obtained show the presence of phytoplankton and algal activity, matching the field observation.
Spectral characterization of water in Itupararanga reservoir, SP, from hyperspectral Hyperion images and derivative analysis
Keywords: Hyperspectral Remote Sensing; Derivative Analysis; Hyperion Sensor; Optically Active Constituents (OACs); Water Quality